Malice in Crimes in Iran and The English Criminal Law - Peyman Rostamian; Mohammad Hossein Hajjarian; Hassan Ali Moazzanzadegan (Jurnal Cita Hukum, 2019)
AbstractThe presence of a psychological relationship between the act and the agent, and the importance of the intent and the classification of crimes into intentional and unintentional crimes, the punishment of the perpetrators of these crimes differed so that today in the distinction between civil and criminal liability, the condition of the psychological element in the proofs of the titles of criminal acts is necessary, so long as it is said that the principle is the deliberate nature of the offenses and the contrary is required to be specified. Therefore, the current paper aims at investigating the malic in crimes in Iran and The United Kingdom. the conceptual research subject is expanded and then, qualitative research method was used to analyze the data collected from library sources using the legal literature analysis method. The findings indicate that: "The psychological element in Iran and The English Criminal Law is in full compliance in some aspects, while and contradictory others. In addition, The English Criminal Law in some cases is more comprehensive in the field of the psychological element, which, along with the sacred Islamic law, can be useful for Iranian law."Keywords: Crime, Moral pillar, Malice, Iranian law, The English Criminal Law AbstrakHubungan psikologis antara tindakan dan agen sangat diperlukan, serta pentingnya mengetahui niat dan klasifikasi atas kejahatan menjadi sebuah kejahatan yang disengaja dan tidak disengaja. Selain hukuman dari pelaku kejahatan ini berbeda hingga saat ini dalam perbedaan antara pertanggungjawaban perdata dan pidana, serta kondisi unsur psikologis dalam pembuktian hak atas tindakan pidana yang diperlukan. Sehingga dapat dikatakan bahwa prinsipnya adalah sifat pelanggaran yang disengaja dan sebaliknya harus ditentukan. Oleh karena itu, makalah ini bertujuan untuk menyelidiki kejahatan dalam kejahatan di Iran dan Inggris. Subjek penelitian konseptual diperluas dan kemudian, metode penelitian kualitatif digunakan untuk menganalisis data yang dikumpulkan dari sumber perpustakaan menggunakan metode analisis literatur hukum. Temuan menunjukkan bahwa: "Unsur psikologis di Iran dan Hukum Pidana Inggris dalam kepatuhan penuh dalam beberapa aspek, sementara dan dan lainnya bertentangan. Selain itu, Hukum Pidana Inggris dalam beberapa kasus lebih komprehensif dalam bidang unsur psikologis, yang, bersama dengan hukum Islam yang sakral, dapat bermanfaat bagi hukum Iran."Kata Kunci: Kejahatan, Pilar Moral, Malice, Hukum Pidana Iran, Hukum Pidana Inggris АннотацияСогласившись с необходимостью наличия психологической связи между деянием и агентом и важностью умысла и классификации преступлений на умышленные и непреднамеренные преступления, наказание лиц, совершивших эти преступления, было разным, поэтому сегодня в различие между гражданской и уголовной ответственностью необходимо наличие психологического элемента в доказательствах названий преступных деяний, при условии, что говорится, что принцип - это преднамеренный характер преступлений, и требуется указать обратное. Таким образом, настоящая статья направлена на расследование преступлений в Иране и Великобритании. Сначала концептуальный предмет исследования расширяется, а затем, качественный метод исследования был использован для анализа данных, собранных из библиотечных источников с использованием метода анализа юридической литературы. Полученные данные указывают на то, что: «Психологический элемент в уголовном праве Ирана и Англии полностью соответствует в некоторых аспектах, хотя и противоречит другим. Кроме того, Уголовное право Англии в некоторых случаях является более полным в области психологического элемента, который, наряду со священным исламским законом, может быть полезен для иранского права».Ключевые Слова: Преступность, Моральная Опора, Злоба, Иранское Право, Английское Уголовное Право